2009
DOI: 10.1016/j.bbrc.2009.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Germline-like predecessors of broadly neutralizing antibodies lack measurable binding to HIV-1 envelope glycoproteins: Implications for evasion of immune responses and design of vaccine immunogens

Abstract: Several human monoclonal antibodies (hmAbs) including b12, 2G12 and 2F5 exhibit relatively potent and broad HIV-1 neutralizing activity. However, their elicitation in vivo by vaccine immunogens based on the HIV-1 envelope glycoprotein (Env) has not been successful. We have hypothesized that HIV-1 has evolved a strategy to reduce or eliminate the immunogenicity of the highly conserved epitopes of such antibodies by using “holes” (absence or very weak binding to these epitopes of germline antibodies that is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
256
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(265 citation statements)
references
References 46 publications
9
256
0
Order By: Relevance
“…ERs for all mutations were calculated by dividing the frequency of a given mutation at a given position in the sorted sample by the frequency of the same mutation in the unsorted sample, as described previously (25,26). Mutagenesis of one segment of V H (position [14][15][16][17][18][19][20][21][22][23][24][25] in the original V H library resulted in errors which led to low expression of the respective segment. This result was likely related to a mutational error in the original stop template used in the mutagenesis reaction for this V H segment 14-25, which affected expression of the variants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERs for all mutations were calculated by dividing the frequency of a given mutation at a given position in the sorted sample by the frequency of the same mutation in the unsorted sample, as described previously (25,26). Mutagenesis of one segment of V H (position [14][15][16][17][18][19][20][21][22][23][24][25] in the original V H library resulted in errors which led to low expression of the respective segment. This result was likely related to a mutational error in the original stop template used in the mutagenesis reaction for this V H segment 14-25, which affected expression of the variants.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, the roles of SHM have been studied primarily by examining the functional consequences of reverting the somatic mutation of selected antibodies back to the germline sequences (15)(16)(17)(18)(19)(20)(21). Although these studies have demonstrated that antibodies depend on somatic mutations to achieve high-affinity antigen binding, the approach is limited to the small set of mutations present in a given antibody.…”
mentioning
confidence: 99%
“…Diversion of pre-existing B cell responses to non-HIV antigens may be at play for some bnAb UCAs as well. Whereas the UCA of some bnAbs interact with Env antigens (15, 17,18, 58, 93), others may not (87, 9497) (Stamatatos, this volume). Thus, an alternative strategy in which non-HIV-1 antigens need be included as immunogens may be necessary to drive the initial maturation of non-HIV-reactive UCAs to maturation intermediates amenable to diversion toward HIV-1 specificity.…”
Section: B Cell Lineage Immunogen Designmentioning
confidence: 99%
“…5,14,17,71 Lastly, homing of B cells to the cervix may allow rescue of B cells with potentially auto-reactive specificity to forbidden epitopes on HIV-1 generated by systemic immunization to the external mucosal environment. 72 The authors note that some level of caution should be taken in extrapolating somatic mutation and mucosal-systemic B-cell trafficking patterns from repertoire analysis conducted on B cells from a single individual. We recognize that a larger and more robust study involving samples from multiple subjects collected at different time points can now be done using cuttingedge technology; however, this study remains as a comparator for the current technology.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%